Active learning in an online postgraduate research module: Perceptions of accounting students and lecturers - Steenkamp, G.; van Schalkwyk, O. (South African Journal of Higher Education, 2023)
Chartered accountancy education offered by universities in South Africa has traditionally been characterised by passive face-to-face (F2F) learning approaches. Literature, however, has pointed out that active learning can enhance student learning, engagement, and motivation. Moreover, employing active online learning could facilitate the development of digital and critical thinking competencies in accounting students, the importance of which is increasingly emphasised. In response to this, a more traditional and passive F2F lecture week (as part of a postgraduate course on research in accounting) was redesigned during the COVID-19 pandemic to be presented fully online, based on the active learning principles found in Laurillard’s Six Ways of Learning. A questionnaire was administered to investigate the perceptions of both students and lecturers as to whether the redesign led to improved learning and competency development, and to increased engagement and motivation. Although some students were resistant to the change in learning approach from passive to active, respondents felt that the active learning tasks led to increased engagement and enhanced learning by students. Student resistance should be managed in future redesign processes to minimise the effect thereof on learning outcomes, possibly through change management principles such as purposeful communication regarding the benefits and requirements of active learning. Respondents reported that the online learning environment provided students with increased flexibility, but that this flexibility had to be managed through self-regulation or monitoring by lecturers. Online learning also led to feelings of disconnect (between lecturers and students, within the student group and in relation to the content). Such disconnect could be alleviated by applying a blended learning approach in future, using the advantages of both the F2F and the online environment. The results of this study are important to lecturers seeking to design courses that engage and motivate students, enhance learning, and allow the development of the competencies required of the accountants of the future.